Discovery of phenoxyindazoles and phenylthioindazoles as RORγ inverse agonists. Issue 23 (1st December 2016) - Ouvry, Gilles; Bouix-Peter, Claire; Ciesielski, Fabrice; Chantalat, Laurent; Christin, Olivier; Comino, Catherine; Duvert, Denis; Feret, Christophe; Harris, Craig S.; Lamy, Laurent; Luzy, Anne-Pascale; Musicki, Branislav; et al.
Graphical abstract: Abstract: Targeting the IL17 pathway and more specifically the nuclear receptor RORγ is thought to be beneficial in multiple skin disorders. The Letter describes the discovery of phenoxyindazoles and thiophenoxy indazoles as potent RORγ inverse agonists. Optimization of the potency and efforts to mitigate the phototoxic liability of the series are presented. Finally, crystallization of the lead compound revealed that the series bound to an allosteric site of the nuclear receptor. Such compounds could be useful as tool compounds for understanding the impact of topical treatment on skin disease models.